Wave discrimination at C-band frequencies in microstrip structures inspired by electromagnetically induced transparency - Abdul Jabbar (Nature Portfolio, 2021)
Abstract We present the design and practical implementation of a microstrip diplexer based on the wave discrimination property associated with the electromagnetically induced transparency (EIT)-like effect. The EIT is a quantum interference phenomenon which happens between two atomic transition pathways and allows wave propagation within a medium’s absorption spectrum. Here, we exploit an analogous interference mechanism in a three-port microstrip structure to demonstrate a diplexer based on the EIT-like effect in the microwave regime. Since the transparency is accompanied by a high transmission and strong dispersion characteristics, compact frequency discriminating structures that can resolve nearby frequencies with high isolation can be devised. Our proposed C-band diplexer consists of pairs of unequal open-circuit stubs, which resonate at detuned frequencies and interfere to form the EIT-like passbands for diplexer action. The design is highly compact and scalable in frequency for both PCB and on-chip applications. A prototype of diplexer is fabricated for the center frequencies of lower and upper passbands at 4.6 GHz and 5.5 GHz respectively. The transmission zeros are designed at the complementary channels so that the two passbands are highly isolated presenting the isolation of about 40 dB. The measured insertion loss of lower and upper passband is 0.59 dB and 0.61 dB respectively. Measured input return loss is better than − 15 dB, while the output return losses are well below − 12 dB. Moreover, a decent value of about 200 is achieved for the group refractive index around the EIT-like passbands, which reveals the slow wave characteristics of the proposed EIT-based diplexer.